Simulação numérica do processo de estampagem a quente do aço USIBOR® 1500P - Fabricio Brandão Pereira de Souza (2013)
Automobile manufacturers have been increasingly adopting hot-stamped parts for use in newly designed vehicles to improve passive automotive safety and reduce vehicle CO2 emissions. The use of quenched boron steel components is an economic way to achieve significant improvements in terms of weight saving and crash performance. Usibor® 1500P, developed by ArcelorMittal, is a precoated boron steel, with an aluminium-silicon metallic coating. The material and process knowledge on the hot stamping of boron steels needs to be extended and accurate simulation tools must be developed to support the growth of this forming technology, including phase transformation modeling in order to predict previously the final mechanical and in-use properties of hot-stamped parts. In the present study, a computer-aided design method incorporating phase transformation kinetic models has been implemented and the capability prediction of the metallurgical models is compared using continuous cooling dilatometry. Hot stamping simulation is performed through the finite elements code LS-DYNA. Numerical and experimental results of hot stamped parts are presented and compared aiming to validate the computational model.